2011
DOI: 10.1111/j.1423-0410.2011.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Placental immunology and maternal alloimmune responses

Abstract: During pregnancy, women are tolerant of their semi-allogeneic fetus whilst not being immunosuppressed and indeed readily form alloantibodies. This 'Immunological Paradox of Pregnancy' may be explained by an understanding of placental anatomy and immunology. Trophoblast cells form the interface between the fetus and maternal tissues and blood and escape allorecognition because they lack classical human leucocyte antigen (HLA) class I and II molecules. Local immunoregulation, or tolerance, in the decidua is medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 80 publications
0
56
0
Order By: Relevance
“…Our previous study also featured patients (N 5 2) with anti-HPA-1a antibodies (normally observed in FNAIT patients) formed after transfusion, and they also did not display a skewing in core fucosylation. 32 Because other glycosylation patterns were affected as well, we hypothesize that this kind of IgG response must be governed by the very settings under which these antibodies are formed: either the T helper 2-dominant features of pregnancies, 39 the anti-platelet response, the anti-HPA-1a response, or a combination of these factors. We also investigated an FNAIT anti-HPA-1a sample, which also contained anti-HLA antibodies, with lowered Fc fucosylation for the anti-HPA-1a antibodies, but not for the anti-HLA antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also featured patients (N 5 2) with anti-HPA-1a antibodies (normally observed in FNAIT patients) formed after transfusion, and they also did not display a skewing in core fucosylation. 32 Because other glycosylation patterns were affected as well, we hypothesize that this kind of IgG response must be governed by the very settings under which these antibodies are formed: either the T helper 2-dominant features of pregnancies, 39 the anti-platelet response, the anti-HPA-1a response, or a combination of these factors. We also investigated an FNAIT anti-HPA-1a sample, which also contained anti-HLA antibodies, with lowered Fc fucosylation for the anti-HPA-1a antibodies, but not for the anti-HLA antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…The developing placenta is a key site of immunity that provides protection for the developing fetus while preventing the maternal immune system from attacking the semi-allogeneic trophoblasts of the fetus 93 . As a placenta grows, intra-placental oxygen gradients are established and HIF becomes activated, even under normal physiological conditions 94 .…”
Section: Hypoxia In Physiological Immune Nichesmentioning
confidence: 99%
“…However, understanding the immunological mechanisms involved in the non-rejection of the placenta by the maternal immune system has been challenging. The placenta, for its embryonic origin, has both maternal and paternal genetic material and can potentially express paternal antigens, which are genetically foreign to the mother and therefore could induce an immune reaction that leads to rejection in a manner similar to that of other grafted tissues [2].…”
Section: Immunological Aspects Of Pregnancymentioning
confidence: 99%
“…The immunological relationship between the mother and the fetus is a bi-directional communication determined on the one hand by fetal antigen presentation and on the other hand by recognition of and reaction to these antigens by the maternal immune system [2].…”
Section: Immunological Aspects Of Pregnancymentioning
confidence: 99%